Rolls-Royce in Singapore: Harnessing the power of the ecosystem to drive growth - DE MEYER, Arnoud (Institutional Knowledge at Singapore Management University, 2014)
This case is set in April 2013, and discusses the key elements that have contributed to the successful operations of the Rolls-Royce Singapore Seletar Campus. The new facility has clearly succeeded in its objective to develop a talent ecosystem of engineering excellence, which would be a key factor in enabling the Group to significantly increase in size as the decade progresses. In 2006, Rolls-Royce had decided to expand its production capacity and set up operations outside the UK to meet growing customer demands and future growth. Asia was the Group’s largest and fastest growing market, with almost half of their new aircraft-engine orders coming from customers in this region. Many of these orders were for the Trent 900, an advanced aero engine that powered the Airbus A380 super jumbo. In order to meet this increased demand, Rolls-Royce helped strategise and facilitate the company’s largest investment to date: the US$565 million (SG$700 million) Seletar Campus - a 154,000 square metre site housing cutting-edge manufacturing, training and research capabilities. The Seletar Campus substantially increased the Group’s global manufacturing capacity for large civil aero engines and wide chord fan blades, complementing existing facilities in the UK. It was expected that by 2015, this facility would effectively double the production output for large Trent aero engines and fan blades. The transfer of knowledge for these advanced aerospace high-value manufacturing techniques was quite a feat, as it was very complex technology that was being introduced for the first time into Asia. Singapore’s Economic Development Board (EDB) was a key enabler of this project, providing unstinted support. However, while building the facility was relatively straightforward; sourcing the right talent was more challenging. The issue of technology and knowledge transfer essentially came down to developing the high-value skills necessary to assemble and test Trent aero engines and manufacture wide chord fan blades to Rolls-Royce standards. Stringent quality control requirements, with an emphasis on manufacturing consistency, necessitated highly trained technicians. Rolls-Royce was committed to growing its own highly-skilled workforce, and invested heavily in training staff with the intention of developing high-value skills through internationally recognised qualification programmes. Rolls-Royce knew that the local labour market lacked enough seasoned aerospace technicians with the desired manufacturing experience to meet their requirements. To overcome this challenge, the Group developed several collaborations with existing and new partners: the Singapore Workforce Development Agency (WDA), National Trade Union Congress’ e2i (Employment and Employability Institute), Singapore Airlines Engineering Company, Institute of Technical Education (ITE) and various polytechnics to develop training and qualifications programmes. This case discusses the challenges encountered, and the way they were overcome, by this public-private partnership that successfully created an ecosystem, which could provide a steady stream of new recruits with the high-value prerequisite skills mandatory for developing quality aerospace technicians.